ANALYSIS OF THE QUALITY OF THE ZETA SCARVES WEBSITE USING THE WEBQUAL 4.0 METHOD - Jumiasih Jumiasih; Maruloh Maruloh (Jurnal Techno Nusa Mandiri, 2024)
This research aims to analyze the quality of the Zeta Scarves website using the WebQual method. The study focuses on three dimensions of website quality: usability, information quality, and service interaction. The data were collected through an online questionnaire distributed to users of the Zeta Scarves website. A total of 296 respondents participated in the study. The collected data were analyzed using descriptive statistics and the WebQual index. The results showed that the Zeta Scarves website received high scores in all dimensions of website quality. The usability dimension, which measures the ease of use and navigation, received a score of 4. The information quality dimension, which assesses the accuracy and relevance of the provided information, received a score of 3,9. The service interaction dimension, which evaluates the customer service and interaction features, received a score of 3,9. Based on the analysis, it can be concluded that the Zeta Scarves website has achieved a high level of quality, as perceived by the users. The findings of this study provide valuable insights for Zeta Scarves in enhancing their website to further improve customer satisfaction and strengthen their competitive position in the online fashion industry